Performance of soybean intercropped under different seed sources of Pongamia pinnata agroforestry system - Inamati, S.S.; Patil, S.J.; Revathi, R. (Indian Journal of Agroforestry, 2020)
Eleven seed sources of Pongamia pinnata were selected from three provenances from Maharashtra, Tamil Nadu and Karnataka to identify suitable seed sources for inclusion in agroforestry condition and study their effect on soybean productivity. Growth attributes viz., height (5.05 m), diameter at breast height (11.86 cm), crown area (4.98 m2/ tree) and number of branches (38.16) were maximum in Pongamia source RAK-89 followed by MTP-II. Maximum leaf dry weight (3.59 g/plant) was found in sole soybean when compared to other Pongamia sources based agroforestry systems. Leaf dry weight was maximum (2.18 & 2.53 g/plant) in MTP-II + soybean and lowest in RAK-90 + soybean (0.44 & 0.74 g/ plant). Maximum stem dry weight of soybean was recorded in RAK-89 + soybean (2.85 & 3.06 g/plant); whereas the treatment MTP-III + soybean (0.10 & 0.26g/plant) had the lowest stem dry weight at 1.5 and 3 m distances from tree base respectively. In soybean as intercrop, the pod dry weight increased significantly in all the Pongamia sources at harvest from 1.5 and 3 m distance from Pongamia row. Seed yield of soybean was maximum in DPS-4+soybean (D1-1.5m and D2-3m; 721.8 and 725.8 kg ha-1) followed by RAK-89 + soybean (D1-1.5m and D2-3m; 674.0 and 678.5 kg ha-1). The yield reduction was to the extent of 58% in MTP-III + soybean as compared to the sole soybean.